PENGEMBANGAN APLIKASI LAYANAN AMBULANS DARURAT BERBASIS ANDROID - Saputra, Ivaldo; Hadi, Ahmaddul (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
The development of an Android-based emergency ambulance service application is needed as a solution to reduce ambulance lending procedures at the hospital, especially when the patient is in an emergency and needs immediate help. For this reason, this service application was developed using the PHP programming language, Android Studio, and MySQL for the database and using the Client-Server method. The purpose of developing this application is to make it easier for the hospital to obtain information on the location of traffic accidents or emergencies that will be faster and more accurate, making it easier for the hospital to maximize handling for victims who need fast service. This application was developed with the Unified Modeling Language (UML) and Entity Relationship Diagram (ERD) model / method with the great-loop approach and evolutionary approach. The results of the development of this system / application show that the application has been completed, which has been tested according to the design and criteria. From the results of the trials carried out, the application is able to run well as expected, so it can be said that the Android-Based Emergency Ambulance Service Application is able to assist in the service process, starting from registration to getting service results.